"Unresolved Complex Mixture" (UCM): A brief history of the term and moving beyond it. Issue 1 (15th July 2015) - Farrington, John W.; Quinn, James G.
Highlights: History of the term "Unresolved Complex Mixture" in hydrocarbons gas chromatograms. Past ten years, the UCM has been partially or fully resolved by analytical methods. Use of the new methods should become routine in oil pollution assessment/research. Abstract: The term "Unresolved Complex Mixture" (UCM) has been used extensively for decades to describe a gas chromatographic characteristic indicative of the presence of fossil fuel hydrocarbons (mainly petroleum hydrocarbons) in hydrocarbons isolated from aquatic samples. We chronicle the origin of the term. While it is still a useful characteristic for screening samples, more modern higher resolution two dimensional gas chromatography and gas chromatography coupled with advanced mass spectrometry techniques (Time-of-Flight or Fourier Transform-Ion Cyclotron Resonance) should be employed for analyses of petroleum contaminated samples. This will facilitate advances in understanding of the origins, fates and effects of petroleum compounds in aquatic environments.